Effect of Oxygen Mixing Percentage on Mechanical and Microwave Dielectric Properties of SrBi4Ti4O15 Thin Films - A. Rambabu; K. C. James Raju; Polamarasetty P. Kumar; Ramakrishna S. S. Nuvvula; Baseem Khan (Advances in Condensed Matter Physics)
Aurivillus oxide thin films with nanostructures attained much interest due to their structural stability, outstanding ferroelectric, and dielectric properties. This manuscript reports the influence of oxygen mixing percentage (OMP) on structural, nanomechanical, and microwave dielectric properties of strontium bismuth titanate (SrBi4Ti4O15) thin films. SrBi4Ti4O15 films were successfully fabricated on fused silica substrates at room temperature, followed by annealed in a microwave furnace. The crystalline nature and purity of the phase was identified by X-ray diffraction. Nanomechanical properties of the SrBi4Ti4O15 films were studied using nanoindentation and nanoscratch tests. The best nanomechanical (hardness ∼6.9 GPa, Young’s modulus ∼120 GPa) properties were shown for films deposited around 50% of OMP. Microwave dielectric properties (dielectric constant and loss tangent at microwave frequencies 10 and 20 GHz) were extracted from the split postdielectric resonator technique.